ON THE DETOUR AND VERTEX DETOUR HULL NUMBERS OF A GRAPH - A. P. Santhakumaran; S. V. Ullas Chandran (Journal of the Indonesian Mathematical Society, 2014)
Abstract PDFDOI : http://dx.doi.org/10.22342/jims.20.1.175.1-9